Komunikasi: Cermatan Perkembangan - Prajarto, Nunung (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2005)
The development of communication rests on the ability to meet the requirements of the government, industry, public and academic motives. Nonetheless, as it also happens in Indonesia, there are five factors that tend to reduce the development. The presence of new media creates another problem in this case. This article presents some endeavors focusing on research to anticipate the development.